Amblyceps accari, a new species of torrent catfish (Teleostei: Amblycipitidae) from the Western Ghats of India - Dahanukar, Neelesh; Raghavan, Rajeev; Ali, Anvar; Britz, Ralf (Zootaxa, 2016)
A new species of torrent catfish, Amblyceps accari, is described from the central region of the Western Ghats of India. The new species differs from all its congeners by having 12 branched anal-fin rays (vs. 7–10 in other Amblyceps, rarely 11 in A. tuberculatum). It differs further from all other species of the genus except A. murraystuarti and A. torrentis in having the adipose fin confluent with the dorsal procurrent part of the caudal fin and by the following combination of characters from all its congeners: jaws unequal with lower jaw weakly-projecting, pectoral spine smooth, adipose-fin origin opposite anal-fin origin, dorsal fin to adipose-fin distance more than one fourth of standard length, adipose fin long with its base more than one-fourth of standard length, and deeply forked caudal fin with minute, poorly developed, centrally projecting hooks on the proximal lepidotrichia of central caudal-fin rays. The discovery of the new species represents the first record of this genus from peninsular India.